2014
DOI: 10.1111/pin.12144
|View full text |Cite
|
Sign up to set email alerts
|

MUC expression in adenosquamous carcinoma of the head and neck regions of Japanese patients: Immunohistochemical analysis

Abstract: Adenosquamous carcinoma (ASC) is a rare malignant neoplasm of the head and neck regions. We elucidated the relationship between ASC and MUC molecule expression. We selected 14 cases of ASC in the head and neck, and examined them immunohistohcmically. Seven cases of tongue, 3 cases of larynx and 4 cases of hypopharynx carcinoma were selected. Nine (64.3%) of 14 cases showed lymph node metastasis at the diagnosis. Laryngeal and hypopharyngeal cases showed a higher stage. Six cases (66.7%), all of which showed ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Considering 18 new cases and 75 reported in the literature available at the time, Masand et al [8] concluded that the larynx was the most common site of ASC in the head and neck, with 45 cases (48.4%). Head and neck ASC is frequently diagnosed in advanced stages (stages III-IV), with regional lymph node metastases in between 44.5% and 66.7% of cases [6][7][8]. Local (11.1%-58.3%), rather than regional (8.3%-11.1%), recurrences are quite common [6][7][8].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering 18 new cases and 75 reported in the literature available at the time, Masand et al [8] concluded that the larynx was the most common site of ASC in the head and neck, with 45 cases (48.4%). Head and neck ASC is frequently diagnosed in advanced stages (stages III-IV), with regional lymph node metastases in between 44.5% and 66.7% of cases [6][7][8]. Local (11.1%-58.3%), rather than regional (8.3%-11.1%), recurrences are quite common [6][7][8].…”
Section: Discussionmentioning
confidence: 98%
“…Head and neck ASC is frequently diagnosed in advanced stages (stages III-IV), with regional lymph node metastases in between 44.5% and 66.7% of cases [6][7][8]. Local (11.1%-58.3%), rather than regional (8.3%-11.1%), recurrences are quite common [6][7][8]. Compared with conventional head and neck SCC, ASC carries a higher rate of distant metastases (24.7%), the lung being the most often affected site [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visualizing components of both AC and SCC in the same tissue sample using light microscopy alone can be challenging, and typically requires confirmation with immunohistochemical markers for each histological type [17] . The complexity inherent in the diagnosis raises the likelihood that ASC can be misdiagnosed as either AC or SCC [8,12,18] .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40]. It is also being used as disease diagnosis [41-45, 23, 26] and prognosis [46] especially for certain carcinomas like breast cancer, colorectal cancer, pancreatic cancer, gastric carcinoma. In this review we explored the role of mucin mainly in non-communicable diseases of various organ systems of the human body like Carcinomas, Gastric carcinoma of stomach, Renal clear cell carcinoma, Medullary Cystic Kidney Disease Type 1 kidney, Inflammatory bowel disease (IBD), Hirschsprung's Disease, …”
Section: Visiting Mucinsmentioning
confidence: 99%